2009
DOI: 10.3390/ijerph6061856
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Control: Visualisation of Research Activity Using Density-Equalizing Mapping and Scientometric Benchmarking Procedures

Abstract: Background:Tobacco smoking continues to be a major preventable cause of death and disease and therefore tobacco control research is extremely important. However, research in this area is often hampered by a lack in funding and there is a need for scientometric techniques to display research efforts.Methods:The present study combines classical bibliometric tools with novel scientometric and visualizing techniques in order to analyse and categorise research in the field of tobacco control.Results:All studies rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 29 publications
2
22
0
1
Order By: Relevance
“…The finding that the United Kingdom and Germany are the biggest producers of tobacco research articles in Europe was also found in previous studies for the period 1999-2003 [12] and 1900-2008 [13] . This is also in line with the United Kingdom and Germany being the two most productive EU countries with respect to overall scientific output [14] .…”
Section: Discussionsupporting
confidence: 85%
“…The finding that the United Kingdom and Germany are the biggest producers of tobacco research articles in Europe was also found in previous studies for the period 1999-2003 [12] and 1900-2008 [13] . This is also in line with the United Kingdom and Germany being the two most productive EU countries with respect to overall scientific output [14] .…”
Section: Discussionsupporting
confidence: 85%
“…Tobacco smoking takes an enormous toll on the global burden of disease (1)(2)(3). Its adverse health effects are attributable to approximately 2,500 toxins in the tobacco plant and approximately 4,000 substances in the tobacco smoke.…”
mentioning
confidence: 99%
“…Using methods similar to those used to study tobacco-related research linkages in the United States19 and globally,20 Dr Gan searched the websites of CNTC and its branch corporations in each province between January 2008 and July 2009 to identify research institutions affiliated with the tobacco companies and relationships between the tobacco companies and academic institutions that conduct tobacco research, including universities (in which we include specialised institutions that are one level below universities in the Chinese higher educational system, known as ‘Zhuanke’ in Chinese) and public research institutions that are owned by the government.…”
Section: Methodsmentioning
confidence: 99%